A Case of Conjunctival Amyloidosis with Repeated Subconjunctival Hemorrhage - Takaaki Ando; Toshiyuki Oshitari; Mamiko Saito; Ayako Tawada; Takayuki Baba; Jiro Yotsukura; Shuichi Yamamoto (Case Reports in Ophthalmological Medicine)
Conjunctival amyloidosis is a very rare disease, and its presence may be a sign of systemic amyloidosis. We present our ocular and systemic findings in a patient with conjunctival amyloidosis. A 43-year-old man had repeated subconjunctival hemorrhages (SCHs) for two years and was referred to the Chiba University Hospital. He had comprehensive ophthalmological and systemic examinations to determine the cause of the SCHs. His visual acuities were 1.2 OU, and the intraocular pressures were 13-14 mmHg OU. Magnetic resonance imaging was normal. Initially, the SCH was the only abnormality. After 3 months, the SCH had partially cleared, and a pink mass was detected in the superior area of the subconjunctiva. Partial biopsy and histopathological examinations showed a greenish birefringence and dichroism under polarized light illumination. The birefringence was located in amyloid fibers. Immunofixation electrophoresis detected λ-light chain abnormality in the ocular biopsy specimen but systemic examinations did not find any lesions. Multiple myeloma was ruled out, and the patient is being followed closely to detect any early signs of systemic amyloidosis. Because repeated SCHs might be initial signs of systemic amyloidosis, patients with conjunctival amyloidosis should be comprehensively examined for systemic amyloidosis because of its poor life prognosis.